Community Health Policy Assessment of a Rural Northeast Missouri County using the Centers for Disease Control and Prevention's CHANGE Tool - Mitch Stewart; Joseph D Visker; Carolyn C Cox (Tabriz University of Medical Sciences, 2013)
Background: In order to build a framework to address policy gaps and needs, community's risk factors were identified and the extent to which current policies were in place to address the risk factors were compared. Methods: Face-to-face interviews, using the US Centers for Disease Con¬trol and Prevention's CHANGE tool were conducted in a rural Northeast Missouri county possessing exceptionally high chronic disease rates to as¬sess the factor(s) had the greatest influence on the rates in each sector of the community. Results: The Health Care Agency sector possessed the most factors cate¬gorized as environmental and policy assets, and the Community-at-Large and Business/Worksite sectors seemed to possess the least environmental and policy factors categorized as assets.Conclusions: Because organizational policies can strongly influence community health practices and behaviors, collaborative leadership from the Health Care Agency sector, comprehensive worksite health promotion programs in the Business/Worksite and Community In¬stitu¬tions/Organizations sectors, and tobacco-free school policies are recom¬mended. Multiple community sectors must work together to change not only behaviors but also environments in this county.